Quantitative fault analysis at Arkitsa, Central Greece, using Terrestrial Laser- Scanning ("LIDAR") - Kokkalas, S.; Jones, R. R.; McCaffrey, K.J. W.; Clegg, P. (Bulletin of the Geological Society of Greece, 2007)
We applied terrestrial laser scanning (ground-based LiDAR) in the Arkitsa fault zone, an area of active extension along the North Evia Gulf in Central Greece. The study area includes well exposed fault surfaces with large accumulated slip and this allowed detailed measurements of the geometry of the fault planes to be acquired. Laser-scan data enable ultra high-resolution three-dimensional digital terrain models of the recently exposed active fault to be created, in order to apply quantitative fault and slip-vector analysis. This study demonstrates the way in which the Arkitsa Fault is segmented on a smaller scale. The variation in dip and strike across individual fault panels is quantified, and shows the extent to which the fault panel surfaces are non-planar. Although the dip of the different fault panels varies considerably, the average orientation of the slip-vectors on the panels are approximately coincident. The fault is steeply oblique sinistral-normal, with average displacement vector plunging 55° towards 340°.